PENGARUH ISOMETRIC HANDGRIP EXERCISE TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI - Apriani Putri, Fuja (STIKES Widyagama Husada, 2024)
Hypertension is a systolic blood pressure of more than 140 mmHg and a diastolic blood pressure of more than 90 mmHg. This research is quantitative with a pre-test design and post-test design. A population of 5,511 cases of hypertension was taken in 2021. A sample of 21 people was taken. Purposive Sampling Technique. Research date 15 June - 12 July 2023. The instrument uses a tension meter to measure systolic and diastolic blood pressure with univariate and bivariate analysis with the Paired Sample T test. The results of research from 21 respondents, systolic blood pressure before the isometric handgrip exercise technique was carried out, obtained a mean value of 157.24, a min max value of 150-160 with a standard deviation of 3,015 and an average diastolic blood pressure mean value of 87.14, a min max value of 79-90 with a standard deviation of 2,575. And the mean value is 141.19, the min max value is 140-145 with a standard deviation of 1,365 and the average diastolic blood pressure, the mean value is 71.52, the min max value is 60-80 with a standard deviation of 5,115. The results of the statistical test showed that the p-value = 0.046 (p <0.05) showed that there was an effect of isometric handgrip exercise on reducing blood pressure in hypertension sufferers in the Simpang IV Sipin Community Health Center Working Area, Jambi City in 2023.